(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Metachromatic leukodystrophy (MLD) is the neurometabolic disease caused by deficiency of enzyme arylsulfatase a resulting in deficiency of sulfatide degradation. The responsible gene is arylsulfatase A gene and is inherited in an autosomal recessive manner. MLD is characterized by three clinical subtypes, defined primarily by age at presentation such as late infantile MLD, juvenile MLD, adult onset MLD. Here we report a case of Juvenile form of MLD that was identified by means of typical history, clinical findings and supported by nerve conduction study, typical MRI of brain findings and confirmed by enzyme assay. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 154-157